1837-1838 Tenn. Pub. Acts 200, ch. 137, § 1. - (:unkn) unknown (General Publisher, 1837)
Prohibited any merchant from selling a Bowie knife or Arkansas tooth pick. Punishable by fine of $100-500 and imprisonment for $1-6 months.
--
Keywords: TRANSFER - NON-GUN ARMS